The reality of the practice of the teachers of the lower basic stage of blended education and its reflection on the application of differentiated education from their point of view in the schools of the Directorate of Education in South Hebron - Amro, Ferial Abdulaziz Mohammad (Journal of Educational and Psychological Sciences, 2023)
This study aims to identify the reality of the practice of the teachers of the lower basic stage of blended education and its reflection on the application of differentiated education from their point of view in the schools of the Directorate of Education south of Hebron. In the Directorate of Education south of Hebron, the study was applied to a sample of (232) male and female teachers who were chosen by the simple random method, The researcher used the questionnaire as a data collection tool. The study concluded that the level of practice of teachers of the lower basic stage of blended education in the Directorate of Education of Hebron was medium, The level of application of differentiated education was average, and the results showed a statistically significant impact of the blended education on the differentiated education of the teachers of the lower basic stage in the Directorate of Education in South Hebron, and the study concluded that there are no statistically significant differences between the averages of the blended and differentiated education among the teachers of the basic stage due to the variables (gender and educational qualification). While differences appeared in years of experience in favor of more than 5 years.